User-centered design and development of a trunk control device for persons with spinal cord injury: A pilot study. (4th July 2022) - Looft, John M.; Sjoholm, Robert; Hansen, Andrew H.; Fairhurst, Stuart; Voss, Greg; Dellamano, Clifford A.; Egginton, Jason; Olney, Christine; Goldish, Gary
Abstract : Context/Objective: There are no wheelchair products designed to allow users to dynamically control trunk posture to both significantly improve functional reach and provide pressure relief during forward lean. This pilot study sought to (1) gather stakeholder desires regarding necessary features for a trunk control system and (2) subsequently develop and pilot test a first-generation trunk control prototype. Design: Multi-staged mixed methods study design. Setting: Minneapolis VA Health Care System, Minneapolis, MN. Participants: Eight people with spinal cord injuries were recruited to participate in a focus group. Five participants returned to discuss, rate, and select a design concepts for prototype development. Two participants returned to test the first-generation trunk control prototype. Interventions: The focus group members selected a trunk control device design that uses backpack straps with a single cable as the most desired option. Our design team then manufactured the first-generation prototype at the Minneapolis VA. Outcome Measures: Bimanual workspace capabilities ( n  = 1) and pressure map relief changes ( n  = 2) during supported forward lean were measured. Both participants also provided feedback on the trunk control devices usability. Results: Bimanual workspace (for Participant 1) was increased by 311% in the sagittal plane with use of the trunk control device as compared to without. Pressure relief during a forward lean was increased with an overall dispersion index reduction of 87.6% and 27.7% for Participant 1 and Participant 2 respectfully. Conclusion: This pilot study successfully elicited desired features for a trunk control device from stakeholders and successfully developed and tested a first-generation trunk control prototype.